Peran Kepemimpinan Militer dan Perceived Organizational Support dalam Meningkatkan Kinerja Personel melalui Organizational Citizenship Behaviour - Garbada Boris Setyawan; Shintya Dewi Saraswati; Nabila Aliffia (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to analyze the role of military leadership and Perceived Organizational Support in improving personnel performance with Organizational Citizenship Behavior as a mediator among military personnel at PUSPENERBAD Lanumad Ahmad Yani Semarang. This study uses a quantitative approach with a sample size of 145 personnel selected representatively. Data analysis techniques were performed using the Partial Least Square (PLS) method with the help of SmartPLS 4.0 software to test the relationship between variables simultaneously. The results showed that military leadership and perceived organizational support had a positive and significant effect on personnel performance. Military leadership and perceived organizational support were able to encourage Organizational Citizenship Behavior. Other findings showed that Organizational Citizenship Behavior contributed significantly in mediating military leadership and perceived organizational support with personnel performance. Thus, it can be concluded that the combination of effective military leadership and strong perceived organizational support can encourage personnel to exhibit high Organizational Citizenship Behavior, which ultimately has a positive impact on improving overall performance at PUSPENERBAD Lanumad Ahmad Yani Semarang.